Skip to main content
\(\newcommand{\id}{\mathrm{id}}\) \( \newcommand{\Span}{\mathrm{span}}\) \( \newcommand{\kernel}{\mathrm{null}\,}\) \( \newcommand{\range}{\mathrm{range}\,}\) \( \newcommand{\RealPart}{\mathrm{Re}}\) \( \newcommand{\ImaginaryPart}{\mathrm{Im}}\) \( \newcommand{\Argument}{\mathrm{Arg}}\) \( \newcommand{\norm}[1]{\| #1 \|}\) \( \newcommand{\inner}[2]{\langle #1, #2 \rangle}\) \( \newcommand{\Span}{\mathrm{span}}\)
Mathematics LibreTexts

1.4: Composition and Inverses

[ "article:topic", "inverse function", "composite function", "authorname:green", "showtoc:no" ]
  • Page ID
    224
  • \( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

    \( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

    Composition of Functions

    Example \(\PageIndex{1}\)

    Sociologists in Holland determine that the number of people \(y\) waiting in a water ride at an amusement park is given by

    \[y = \dfrac{1}{50}C^2 + C + 2 \nonumber \]

    where \(C\) is the temperature in degrees \(C\). The formula to convert Fahrenheit to Celsius \(C\) is given by

    \[C = \dfrac{5}{9}F + \dfrac{160}{9}. \nonumber \]

    To get a function of \(F\) we compose the two function:

    \[y(C(F)) = \left(\dfrac{1}{50}\right)\left[\dfrac{5}{9}F + \dfrac{160}{9}\right]^2 + \left[\dfrac{5}{9}F + \dfrac{160}{9}\right] + 2 \nonumber \]

    Exercise \(\PageIndex{1}\)

    If 

    • \(f(x) = 3x + 2\)
    • \(g(x) = 2x^2 + 1\)
    • \(h(x) = \sqrt{x-2}\)
    • \(c(x) = 4\)

    Find

    1. \(f(g(x))\)
    2. \(f(h(x))\)
    3. \(f(f(x))\)
    4. \(h(c(x))\)
    5. \(c(f(g(h(x))))\)

    1-1 Functions

    Definition: 1-1 (one-to-one)

    A function \(f(x)\) is 1-1 if 

    \[f(a) = f(b)\]

    implies that

    \[a = b.\]

    Example \(\PageIndex{2}\)

    If

    \[f(x) = 3x + 1 \nonumber\]

    then

    \[3a + 1 = 3b + 1 \nonumber\]

    implies that

    \[3a = 3b \nonumber\]

    hence

    \[a = b \nonumber\]

    therefore \(f(x)\) is 1-1.

    Example \(\PageIndex{3}\)

    If

    \[f(x) = x^2 \nonumber\]

    then

    \[a^2 = b^2 \nonumber\]

    implies that 

    \[a^2-b^2 = 0 \nonumber\]

    or that

    \[(a - b)(a + b) = 0 \nonumber\]

    hence

    \[a = b \text{ or } a = -b \nonumber\]

    For example

    \[f (2) = f (-2) = 4 \nonumber\]

    Hence \(f(x)\) is not 1-1.

    Horizontal Line Test

    If every horizontal line passes through \(f(x)\) at most once then \(f(x)\) is 1-1.

    oneone.gif

    Inverse Functions

    Definition: Inverse function

    A function \(g(x)\) is an inverse of \(f(x)\) if

    \[f(g(x)) = g(f(x)) = x.\]

    Example \(\PageIndex{4}\)

    The volume of a lake is modeled by the equation

    \[V(t) = \dfrac{1}{125}h^3. \nonumber\]

     Show that the inverse is

    \[h(N) = 5V^{\frac{1}{3}}. \nonumber\]

    Solution: We have

    \[h(V(h)) = 5(\dfrac{1}{125}h^3)^{\frac{1}{3}} = \dfrac{5}{5}h = h \nonumber\]

    and 

    \[v(h(V)) = \dfrac{1}{125}(5V^{\frac{1}{3}})^3 = \dfrac{1}{125}(125V) = V. \nonumber\]

    Step by Step Process for Finding the Inverse

    1. Interchange the variables
    2. Solve for \(y\)
    3. Write in terms of \(f^{-1}(x)\)

    Example\(\PageIndex{5}\)

    Find the inverse of 

    \[f (x) = y = 3x^3 - 5 \nonumber\]

    Solution:

    \[\begin{align} x &= 3y^3 - 5 \\ x + 5 &= 3y^3 \\ \dfrac{(x + 5)}{3} &= y^3 ,\\ \left[\dfrac{(x + 5)}{3}\right]^{\frac{1}{3}}&=y \end{align}\]

    \[f^{-1}(x) = \left[\dfrac{(x + 5)}{ 3 }\right]^{\frac{1}{3}}. \nonumber\]

    Graphing

    To graph an inverse we draw the \(y = x\) line and reflect the graph across this line.

    To interactively view the graph of an inverse click here:

    http://mathcsjava.emporia.edu/~greenlar/Inverse/inverse.html

    Contributors